Translation and Analysis of Selected Maguindanaon Folktales: Basis for Developing Comics as Teaching Materials - MANGINDLA, FERDOS (International Journal of Arts, Sciences and Education, 2025)
The folktales of the Maguindanaon people reflect their rich culture, history, and identity. This study aims to translate and analyze selected Maguindanaon folktales as a basis for developing comics as instructional materials. It also seeks to identify the material and non-material cultural elements present in these folktales and to assess the validity and acceptance of the developed comics in the classroom setting. The folktales were collected from Barangay Sisiman in Lutayan, Sultan Kudarat. Twenty teachers and students from Lutayan National High School evaluated the comics. A descriptive-developmental method was used to guide the translation, analysis, and creation of the comics, with the goal of enhancing local literature instruction. Results showed that the translation was appropriate, as validated by Maguindanaon teachers. The folktales were found to be rich in cultural content, and the comics received a high validity rating. Both teachers and students positively accepted the material, indicating its effectiveness. The study concludes that creative approaches, such as using comics based on local literature, can effectively promote student engagement and learning.